Nitric Oxide Scavenging Activity of Bioactive Compounds Present in Methanolic Extract of Morchella esculenta - Baba, D. R.; Junaid, P. M.; Khan, F.; Singh, R. (International Journal of Scientific Research in Biological Sciences, 2018)
Morchella esculenta is commonly known as morel, common morel, true morel, yellow morel, sponge morel and morel mushroom [1]. It is one of the most easily recognized of all the edible mushrooms and highly sought after. Morchella mushroom is one of the costliest edible fungi in the world. Morchella esculenta is in economically important mushroom commonly known as “Guchhi” in India. In India, the presence of Morchella is reported from Himachal Pradesh, Uttar Pradesh and Jammu and Kashmir [2]. It has been reported that the morel species are good to minimize the oxidative damage in organisms that occur in several chronic diseases. Moreover, these morel species can be used to find new antimicrobials overlapping the resistance of bacteria to first choice antibiotics. The compounds like Phenol, Tocopherol and organic acids are considered to be the most responsible for antioxidant activity of mushrooms [3][4]. Methanol extract of Morchella esculenta was screened to evaluate free radical scavenging effect. The extract exhibited significant reducing power and free radical scavenging effect on nitric oxide radicals. This antioxidant activity was concentration dependent which were compared with standard antioxidants such as ascorbic acid. The highest free radical scavenging effect of the extract was observed at concentration of 100μg/ml and the IC50 value of extract was 49.8821μg/ml.